Effect of wrist position on distal radioulnar joint stability: A biomechanical study. Issue 10 (25th June 2014) - Iida, Akio; Omokawa, Shohei; Moritomo, Hisao; Omori, Shinsuke; Kataoka, Toshiyuki; Aoki, Mitsuhiro; Wada, Takuro; Fujimiya, Mineko; Tanaka, Yasuhito
ABSTRACT We investigated distal radioulnar joint (DRUJ) stability in different wrist positions and examined the relative contribution of each ligamentous component of the triangular fibrocartilage complex (TFCC) to DRUJ stability. We used nine fresh‐frozen cadavers. The humerus and ulna were fixed at 90° elbow flexion. The radiocarpal unit was translated relative to the ulna in dorsopalmar directions with the wrist in five positions. Displacement of the unit was measured by an electromagnetic tracking device. Magnitudes of displacement were compared between different wrist positions in various sectioning stages: ulnocarpal ligament (UCL) sectioning, radioulnar ligaments (RUL) sectioning, and extensor carpi ulnaris (ECU) floor sectioning. Wrist position and sectioning stage significantly influenced the displacement. In intact wrists, the displacement in wrist extension was significantly lower than that in neutral. However, after UCL sectioning, there were no longer any significant differences. After RUL sectioning, the displacement in radial deviation was significantly lower than that in neutral. Following ECU floor sectioning, there were no longer any significant differences. Thus, in intact wrists, DRUJ stability in wrist extension is likely due to tightening of the UCL. After complete RUL sectioning, DRUJ is stabilized in radial deviation due to tightening of the ECU floor. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1247–1251, 2014.